Effects of Sintering Temperature on Crystallinity, Morphology, and Photocatalytic Activity of Bi2O3 (International Journal of Scientific Research and Management (IJSRM), 2019)
Bi2O3 has successfully been synthesized using precipitation method with sintering temperature variations of 400oC, 450o C, 500o C, 550o C, and 600o C. Crystallinity property of resulting Bi2O3 powder has also been tested with XRD and morphology properties were tested with SEM. Meanwhile, photocatalytic properties were tested by using it to degrade Rhodamine B under sunlight. Results of XRD tests show that differences in sintering temperature affect crystallite size. Increases in sintering temperature between 400o C and 500o C result in greater crystallite size, whereas sintering temperature between 550o C and 600oC result in smaller crystallite size. Results of SEM tests show that resulting Bi2O3 has rod-like structure, While results of degradation tests show that increases in sintering temperature enhances photocatalytic activities of Bi2O3, as evident with Bi2O3 undergoing sintering at 600oC was able to degrade Rhodamine B with 56.74% effectiveness and degradation rate of 0.007 ppm/min.